Crack Resistance of Weld Seals, Hardening Methods and Composite Tools Quality; Applied Mechanics and Materials; Vol. 682 : Innovation Technology and Economics in Engineering - Petrova V. A. (Material Science, Machining Technologies and Equipments in Mechanical Engineering, 2014)
Title screen